Concrete Grinding Residue: Management Practices and Reuse for Soil Stabilization. Issue 11 (November 2019) - Yang, Bo; Zhang, Yang; Cetin, Bora; Ceylan, Halil
Concrete grinding residue (CGR) is a slurry byproduct produced from diamond grinding operations used to smooth concrete pavement surface. As a waste material, CGR consists of cooling water for blades and concrete fines from the removed concrete layer. Since the composition of CGR reflects high pH, it can be a critical environmental issue and should be managed properly to reduce its impact to the ecological system. To understand the current management practices of CGR throughout the U.S.A., a comprehensive review of state regulations and a survey of departments of transportation and contractors were conducted in this study, with results showing that in many states detailed guidance for disposal of CGR to reduce risks was lacking. In addition, this study investigated the potential use of CGR for roadbed soil stabilization. To evaluate the performance of CGR for soil stabilization purpose, this study mixed 10%, 20%, 30%, and 40% of CGR by weight with two types of soils classified as A-4 and A-6 according to AASHTO. Unconfined compressive strength and California bearing ratio, pH, electrical conductivity, alkalinity, and cation-exchange capacity tests were conducted on specimens. Results of the strength tests showed that the soils treated with 20% of CGR had the highest strength. Other laboratory tests revealed that CGR treatment could reduce the maximum dry unit weight (γdmax ) and plasticity and increase the pH, alkalinity, electrical conductivity and cation-exchange capacity of soils.